Does Changing Behavioral Intentions Engender Behavior Change? A Meta-Analysis of the Experimental Evidence. [article].
Numerous theories in social and health psychology assume that intentions cause behaviors. However, most tests of the intention-behavior relation involve correlational studies that preclude causal inferences. In order to determine whether changes in behavioral intention engender behavior change, participants should be assigned randomly to a treatment that significantly increases the strength of respective intentions relative to a control condition, and differences in subsequent behavior should be compared. The present research obtained 47 experimental tests of intention-behavioral relations that satisfied these criteria. Meta-analysis showed that a medium-to- large change in intention (d =0.66) leads to a small-to-medium change in behavior (d = 0.36). The review also identified several conceptual factors, methodological features, and intervention characteristics that moderate intention-behavior consistency.-- (from the author)
Keywords: Intention; Behavior change; Intervention; Meta-analysis.